Thermally activated martensite formation in ferrous alloys. (1st January 2018) - Villa, Matteo; Somers, Marcel A.J.
Abstract: Magnetometry was applied to investigate the formation of α / α ´ martensite in 13 ferrous alloys during immersion in boiling nitrogen and during re-heating to room temperature at controlled heating rates in the range 0.0083–0.83 K s − 1 . Data shows that in 3 of the alloys, those that form 5 5 7γ martensite, no martensite develops during cooling. For all investigated alloys, irrespective of the type of martensite forming, thermally activated martensite develops during heating . The activation energy for thermally activated martensite formation is in the range 8–27 kJ mol − 1 and increases with the fraction of interstitial solutes in the alloy. Graphical abstract: